Passiflora metae, a new species of Passiflora series Laurifoliae (Passifloraceae) of the Andean piedmont in the Colombian Orinoquia - Bonilla Morales, Miguel Macgayver; Aguirre-Morales, Adriana Carolina; Caetano, Creucí María (Phytotaxa, 2016)
A new species, Passiflora metae of the supersection Laurifolia ser. Laurifoliae occurring in Andean Colombia, on the eastern piedmont of the Cordillera Oriental in the Meta Department, is described and illustrated. Passiflora metae differs from the most morphologically closely related species of this series, P. nitida and P. acuminata, by its elliptical leaves with cuspidate apex, ensiform bracts (15–20 × 4.5–5 mm) with prominent glands, lanceolate sepals, corona with 5 series of filaments, slender, outermost 2 series, banded red and white at base, purple and white towards the apex, ovary ellipsoid and glabrous. Information about its habitat, ecology, distribution and conservation is provided. Taxonomic comments on the related species are also included. A key to the Colombian species of Passiflora series Laurifoliae and an updated list of the species that belong to the series Laurifoliae for Meta Department is presented.